[(bpy)CuSCF3]: A Practical and Efficient Reagent for the Construction of C–SCF3 Bonds - Huang, Yangjie; Zhang, Mengjia; Lin, Qi; Weng, Zhiqiang (Synlett, 2021)
In this account, we summarize recent work on the direct introduction of the SCF3 group by using [(bpy)CuSCF3] as trifluoromethylthiolating reagent. A number of efficient and convenient strategies have been disclosed for the synthesis of trifluoromethylthiolated compounds, including trifluoromethylthiolation of aryl, alkenyl, and alkyl halides, and arylboronic acids. These reactions afford various trifluoromethyl sulfides in good yields.1 Introduction2 Synthesis of [(bpy)CuSCF3]3 Trifluoromethylthiolation of Aryl Halides4 Trifluoromethylthiolation of Alkenyl Halides5 Trifluoromethylthiolation of Alkyl Halides6 Miscellaneous7 Conclusion
Keywords: trifluoromethylthiolation; copper; fluorine; trifluoromethylthiolating reagent